Hypnotherapy for agoraphobia—Feasibility and efficacy investigated in a pilot study - Fuhr, Kristina; Bender, Annika; Wiegand, Ariane; Janouch, Paul; Drujan, Marta; Cyrny, Barbara; Schweizer, Cornelie; Kreifelts, Benjamin; Nieratschker, Vanessa; Batra, Anil (Frontiers in Psychology, 2023)
A number of case studies describing hypnotherapy in the treatment of anxiety disorder patients have been already published. Only few randomized controlled trials (RCTs) investigated the efficacy of hypnotherapy but focusing mainly on symptoms rather than specific mental disorders. The goal of this study was to investigate whether hypnotherapy (HT) was superior to a wait-list control group (WL) in the reduction of agoraphobia-related symptoms. Further goals were to report the feasibility of hypnotherapy as well as attrition and completion rates and detect (epi-)genetic variables which might play a role for treatment outcome. This pilot study was based on a monocentric two-armed randomized controlled rater-blind clinical trial with a wait-list control group that was conducted between 2018 and 2020. A total of 36 patients diagnosed with agoraphobia were randomized to either HT or WL. Patients in HT received individual outpatient treatment with hypnotherapy with 8 to 12 sessions for a period of three months. Patients in WL received HT after three months. Agoraphobia related symptoms were assessed at baseline, after the treatment and three months later in both groups with a clinician-rating. The primary hypothesis concerning the difference between groups in the individual percentage symptom reduction could be confirmed in the intention-to-treat, not the per protocol sample. Additionally, we applied repeated measures analyses of variance and found a higher symptom decrease in HT compared to WL patients in three of the five imputed datasets. Dropout rate was low and satisfaction with the treatment high. HT patients experienced a strong symptom reduction after receiving hypnotherapy. WL patients improved slightly during the waiting period. The COMT Val108/158Met genotype had an effect on the agoraphobia-related symptoms as well as on COMT DNA methylation levels. This is the first study to indicate that hypnotherapy performed better than a wait-list control group regarding the reduction of the anxiety symptoms in an RCT. Future studies should confirm the efficacy of hypnotherapy and compare the treatment with a standard treatment in anxiety disorders in a larger trial. Future studies should also investigate if hypnotic susceptibility is associated with COMT Val108/158Met genotype and could predict treatment success for HT.